Quantity Controls, License Transferability, and the Level of Investment - Tan, Ling (IMF Working Papers; Working Paper ;, 2001)
This paper models investment/entry decisions in a competitive industry that is subject to a quantity control on an input for production. The quantity control is implemented by auctioning licenses for the restricted input (e.g., a pollution permit or a production license). The paper shows that liberalizing the quantity control could reduce investment in the industry under certain circumstances. Furthermore, the level of investment is quite different when licenses are tradable than when they are not. Key factors in the comparison include the elasticity of demand for the final good and the degree of input substitutability. Two examples are computed to illustrate the results.